Boosting Critical Thinking: A Prominent Aspect to Uphold Learners’ Autonomy in the EFL Classroom - Addinna, Ainul; Oktaviani, Lulud (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2023)
This paper clarifies how learners' critical thinking could promote their autonomy in EFL classrooms. The study's findings contain opinions collections of Seventeen undergraduate students from the English Department of Universitas Negeri Padang. they took a Critical Reading course for a semester. This study analyzed toward their responsibilities in learning, confidence in operating their autonomy, and motivation that build up as well assist them in exploring reading texts. The good thing is that they can fully participate in classroom activities and discover themselves enjoy looking for more information about the reading. Students who reach this stage of thinking are believed to be critical and independent.